Mythology and lament : studies in the oracles about the nations in Isaiah 13-23, Jeremiah 46-51 and Ezekiel 26-32 /: studies in the oracles about the nations in Isaiah 13-23, Jeremiah 46-51 and Ezekiel 26-32. (2017) - Unknown
No abstract available